SUBSTITUTION OF CORN USING CASSAPRO (CASSAVA PROTEIN) IN FEED ON PERFORMANCES OF KAMPUNG CHICKEN - B B Benara; I Sembiring; E Mirwandhono; Hamdan Hamdan; T H Wahyuni (Jurnal Peternakan Integratif, 2017)
Abstract. This research was conducted at The Animal Biology Laboratory, Faculty of Agriculture, SumateraUtara University from December 2015 to March 2016. This research aimed to determine the ability of cassapro to substitute corn in feed on the performances of kampung chicken. Experimental design used in this research was completely randomized design (CRD) with 5 treatments and 4 replications. Each treatment consisted of comparison between corn and cassapro at ratio 60:0 (P0), 50:10 (P1), 40:20 (P2), 30:30 (P3), 20:40 (P4). 100 kampung chickens was used in this research with replications consists of 5 DOC.   The results showed that the average of feed consumption (g/head/week) on treatment P0, P1, P2, P3 and P4 respectively 327,9; 327,3; 326,93; 325,77 and 326,33. The average of body weight gain (g/head/week) on treatment P0, P1, P2, P3 and P4 respectively 56,46; 59,47; 60,79; 56,44 and 56,74 also the FCR on treatment P0, P1, P2, P3 and P4 respectively 5,82; 5,52; 5,38; 5,79 and 5,7. The anova result showed that there is no difference from treatments on tested parameters. The conclution of this research is that cassapro have the ability to substitute corn in kampung chicken’s feed. Keywords: Cassapro, corn, kampung chicken, performance, substitution